Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content: 1. The relationship between international financing and domestic investment efficiency in Financing Development in the State of Palestine Mr. Mahmoud Gawdat Mahmoud Qabaha, Dr. Abdul-Rahim Salim Shobaki 2. The Impact of Management by wandering Around on the Perception of Organizational Justice from the Perspective of Employees in the Directorates of the Jordanian Ministry of Education Mr. Ahmad Abdallah Obeidat, Dr. Riad Ahmad Aba Zaid 3. The effectiveness of the human resources management strategy in improving employee performance by applying it to Meera Company in Asir Region Mrs. Maha Mushabab Ali Al-Qahtani, Mrs. Ebtisam Mohammed Khalid Fara, Mrs. Wejdan Mana Saeed Al- Qahtani, Dr. Abdullah Mahmoud Mohamed Badr 4. Disciplinary Responsibility of the Government Employee in the Law of Saudi Arabia Dr. Hashem Baker Alshaikh 5. Cloud Computing and The Future of Higher Education Institutions Mr. Bekkari Mokhtar 6. The role of transformational leadership in improving the performance of the Hajj and Umrah system Mr. Mohammad Saad Al-Ghalbi